Efforts to Improve the Development of Language and Reading Children with the Story and Play Method - Rahmi Pitri Yenni (Universitas Negeri Padang, 2020)
Language development and reading in children is still at a low level. This is seen from observations in the field. The purpose of this study is to improve reading and listening skills in children with the method of fairy tales and play in kindergarten Pembina Lubuk Basung. In conducting this research using observation techniques and assessment formats. Based on the results of the study it can be concluded that the method of fairytale and play can improve language and reading skills in early childhood in TK Pembina Lubuk Basung.Keywords: Language Development, Reading, Fairy Tales, Play